Heading Date QTL in Winter Wheat (Triticum aestivum L.) Coincide with Major Developmental Genes VERNALIZATION1 and PHOTOPERIOD1 - Guedira, Mohammed (PLoS One, 2016)
In wheat (Triticum aestivum L.), time from planting to spike emergence is influenced by genes controlling vernalization requirement and photoperiod response. Characterizing the available genetic diversity of known and novel alleles of VERNALIZATION1 (VRN1) and PHOTOPERIOD1 (PPD1) in winter wheat can inform approaches for breeding climate resilient cultivars. This study identified QTL for heading date (HD) associated with multiple VRN1 and PPD1 loci in a population developed from a cross between two early flowering winter wheat cultivars. When the population was grown in the greenhouse after partial vernalization treatment, major heading date QTLs co-located with the VRN-A1 and VRN-B1 loci. Copy number variation at the VRN-A1 locus influenced HD such that RIL having three copies required longer cold exposure to transition to flowering than RIL having two VRN-A1 copies. Sequencing vrn-B1 winter alleles of the parents revealed multiple polymorphisms in the first intron that were the basis of mapping a major HD QTL coinciding with VRN-B1. A 36 bp deletion in the first intron of VRN-B1 was associated with earlier HD after partial vernalization in lines having either two or three haploid copies of VRN-A1. The VRN1 loci interacted significantly and influenced time to heading in field experiments in Louisiana, Georgia and North Carolina. The PPD1 loci were significant determinants of heading date in the fully vernalized treatment in the greenhouse and in all field environments. Heading date QTL were associated with alleles having large deletions in the upstream regions of PPD-A1 and PPD-D1 and with copy number variants at the PPD-B1 locus. The PPD-D1 locus was determined to have the largest genetic effect, followed by PPD-A1 and PPD-B1. Our results demonstrate that VRN1 and PPD1 alleles of varying strength allow fine tuning of flowering time in diverse winter wheat growing environments.